Effect of stocking density on the welfare, haematology and serum biochemical indices of broiler chickens (2011)
Influence of stocking density on welfare parameters (Litter temperature and moisture, microbial load, Gait score), haematology and serum biochemical indices (as indicators of condition of stress) on broilers was studied in an eight week feeding trial. A total of 240 one- day old Arbor acre broiler chicks were randomly allotted to three treatments (stocking densities) with 4 replicates each having 20 birds per replicate. The stocking densities rates were 10birds/m2, 12birds/m2 and 14 birds/ m2 respectively. Data obtained were subjected to one way analysis of variance. Serum biochemical indices and microbial load were not significantly (p>0.05) influenced by the treatments. A fraction of haematology, the haemoglobin (Hb) and eosinophil (Eos) were significantly (p<0.05) influenced by different stocking densities. Microbial toad, Utter moisture and temperature increased linearly with increasing stocking density across the treatments. Blood profile of the broiler chickens indicated no negative effect of stocking density except on Hb and Eos which reflected the packed condition of the birds. In conclusion, stocking density of 10birds/m2 can be recommended as birds fared best under this treatment.